2010
DOI: 10.1016/j.clinthera.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of vancomycin pharmacodynamics in children with invasive methicillin-resistant Staphylococcus aureus infections: A Monte Carlo simulation

Abstract: Background Due to the emergence of community-associated strains, the prevalence of invasive methicillin-resistant Staphylococcus aureus (MRSA) infections has increased substantially in pediatric patients. A vancomycin AUC0–24/MIC index >400 best predicts treatment outcomes for invasive MRSA infection in adults. Data on whether recommended vancomycin doses in children achieve this break point are lacking. Objective This study aimed to assess the likelihood that currently recommended vancomycin doses in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…21 A second study showed that vancomycin troughs of 7 to 10 mg/L are likely predictive of AUC:MIC >400 when using a dosing regimen of 15 mg/kg per dose every 6 hours. 22 Based on this modeling, it may not be necessary to achieve troughs of 15 to 20 mg/L to achieve an AUC:MIC >400 in pediatric patients.…”
Section: Discussionmentioning
confidence: 98%
“…21 A second study showed that vancomycin troughs of 7 to 10 mg/L are likely predictive of AUC:MIC >400 when using a dosing regimen of 15 mg/kg per dose every 6 hours. 22 Based on this modeling, it may not be necessary to achieve troughs of 15 to 20 mg/L to achieve an AUC:MIC >400 in pediatric patients.…”
Section: Discussionmentioning
confidence: 98%
“…For neonates, lower targets may suffice as most of the identified infectious organisms are coagulase-negative staphylococci instead of MRSA (11,12). It has been reported that if the MIC is Ͻ1 mg/ liter, 60 mg/kg/day seems necessary to reach an AUC 24 /MIC of Ͼ400 in children (20,(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…2 Many studies 7,14,17 have used AUC/MIC greater than or equal to 400 as a target for pediatric patients; however, in parallel with target serum trough levels, AUC/MIC has not been studied or verified in pediatric populations to correlate particular ratios with clinical outcomes. In their retrospective cohort study, Le and others 14 examined achievement of AUC/MIC in pediatric patients and highlighted that clinicians may be achieving target AUC/MIC of 400 or greater, despite apparently subtherapeutic trough levels.…”
Section: Discussionmentioning
confidence: 99%